Pengaruh ukuran perusahan, profitabilitas dan leverage terhadap nilai perusahaan (studi pada perusahaan sektor perbankan yang terdaftar di bei tahun 2018-2022) - Uray Andrey Indra Maulana (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2023)
This study was conducted to determine the effect of company size, profitability, and leverage on firm value. This research method is quantitative, with the number of samples in this study totaling 30 banking sector companies that use sampling techniques, namely the purposive sampling method. The data analysis technique used is multiple linear regression analysis, which aims to test the hypothesis in this study.The results of this study indicate that the firm size variable affects firm value, profitability affects firm value, and leverage affects firm value. Simultaneously, the three variables have an influence of 55.7% on firm value, and variables outside the study influence 44.3%.Keywords: Firm Size, Profitability, Leverage, Firm Valu